2005
DOI: 10.1080/09273940590951061
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Treatment with Immunomodulatory Therapy in Patients with Corticosteroid-Resistant Juvenile Idiopathic Arthritis-Associated Chronic Iridocyclitis

Abstract: We noted improvement or maintenance of visual acuity (86%) during the course of follow-up of patients with treatment-resistant JIA-associated uveitis treated with effective IMT. However, only IMT given early in the disease course was noted to be associated with bilateral visual acuity of 20/30 or better.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 22 publications
0
32
1
1
Order By: Relevance
“…Nevertheless, avoidance of moderate vision loss provides an adequate indication to advocate use of immunosuppressive therapy in patients with chronic uveitis related to JIA. Given evidence supporting the relative safety and effectiveness of immunosuppressive drug therapy in the treatment of a variety of ocular inflammatory diseases, 2333 the threshold for starting immunosuppression in cases that are not easily and stably controlled by simpler means should be low. Our ability to conduct sub-analyses investigating various types of IMT was limited by indication for treatment bias, as drugs typically employed for more severe cases would tend to have worse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, avoidance of moderate vision loss provides an adequate indication to advocate use of immunosuppressive therapy in patients with chronic uveitis related to JIA. Given evidence supporting the relative safety and effectiveness of immunosuppressive drug therapy in the treatment of a variety of ocular inflammatory diseases, 2333 the threshold for starting immunosuppression in cases that are not easily and stably controlled by simpler means should be low. Our ability to conduct sub-analyses investigating various types of IMT was limited by indication for treatment bias, as drugs typically employed for more severe cases would tend to have worse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…JIA-associated uveitis frequently has been reported to result in visual impairment as a result of structural ocular complications such as cataract 1,6,7,9,19. We reviewed our experience with JIA-associated uveitis over 21 years in order to estimate in the effect of treatment with topical corticosteroids on the development of cataract over time.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that patients who received immunomodulatory therapy early in the course of steroid resistant JIA uveitis, had better visual acuity than patients who received it later. 13 Increased treatment of JIA in childhood with methotrexate and tumor necrosis factor-alpha blocking agents may decrease adult uveitis, but this has yet to be established. 12 , 14 This series suggests that active uveitis in adults who have had JIA as children, is often associated with ongoing complications at a rate that is higher than other series of chronic uveitis in adults.…”
Section: Discussionmentioning
confidence: 99%